SISTEM PENDIDIKAN PONDOK PESANTREN DARUL HABIBI NAHDATUL WATHAN (NW) PAOK TAWAH PRAYA LOMBOK TENGAH. - satria umami (SOLID, 2018)
Abstract: Boarding schools as education providers, selectively aimed at making students a reliable resource and expected to become leader of the Muslims, therefore the system or system component of education boarding schools should be improved.The focus of this research is to examine the system of education boarding schools Darul Habibi Nahdatul Wathan Paok Tawah Praya central Lombok in pursuit of goals that are explained in the formulation of the problem: 1) how the system of education boarding schools Darul Habibi Nahdatul Wathan Paok Tawah Praya central Lombok 2) how the relationship component of the education system in achieving the objectives. Keywords: Educational Boarding Schools System, System Component in Achieving Goals Abstrak: Pondok pesantren sebagai penyelenggara pendidikan Islam, secara  selektif bertujuan menjadikan sumber daya santri yang handal dan diharapkan dapat menjadi pimpinan umat Islam, oleh karena itu sistem atau komponen sistem  pendidikan  pondok pesantren harus ditingkatkan. Fokus dari penelitian ini untuk mengkaji sistem pendidikan pondok pesantren Darul Habibi Nahdatul Wathan Paok Tawah Praya Lombok Tengah dalam mencapai tujuan yang di jelaskan dalam rumusan masalah: 1) Bagaimana Sistem Pendidikan Pondok Pesantren Darul Habibi Nahdatul Wathan Paok Tawah Praya Lombok Tengah 2) Bagaimana Hubungan Komponen Sistem   Pendidikan Dalam Mencapai Tujuan. Kata Kunci: Sistem Pendidikan Pondok Pesantren, Hubungan Komponen Sistem Dalam Mencapai Tujuan